Managing Marine Protected Areas in Remote Areas: The Case of the Subantarctic Heard and McDonald Islands - Brooks, Cassandra M.; Epstein, Graham; Ban, Natalie C. (Frontiers in Marine Science, 2019)
Large marine protected areas (MPAs) are increasingly being established to contribute to global conservation targets but present an immense challenge for managers as they seek to govern human interactions with the environment over a vast geographical expanse. These challenges are further compounded by the remote location of some MPAs, which magnify the costs of management activities. However, large size and remoteness alone may be insufficient to achieve conservation outcomes in the absence of critical management functions such as environmental monitoring and enforcement. The Australian subantarctic Heard Island and McDonald Islands (HIMI) Marine Reserve is among the world’s most remote MPAs with notoriously harsh oceanographic conditions, and yet the region’s rich mammal and fish resources have been exploited intermittently since the mid-1800s. More recently, the development of lucrative international markets for Patagonian toothfish, sold as Chilean seabass, led to the growth in both legal and illegal fishing. In 2002, to conserve the unique ecology and biodiversity in the area, Australia declared a 65,000 km2 MPA around HIMI. Worldwide, government agencies have, however, struggled to develop cost-effective institutional arrangements for conservation. This paper therefore draws upon the social-ecological systems meta-analysis database (SESMAD) to characterize the structure of conservation governance and outcomes in the HIMI Marine Reserve. The Marine Reserve has generally been successful in supporting a sustainable fishery while addressing threats to biodiversity. The remote and isolated nature of the Marine Reserve was critical to its success, but also benefited greatly from collaborations between managers and the fishing industry. Commercial fishers keep watch over the Reserve while fishing, report any observations of illegal fishing (none since 2006/07), and have at times been asked to verify remote observation of potential illegal fishing vessels. The industry also undertakes annual ecological surveys in the MPA, allowing managers to track environmental trends. The fishing industry itself highlights the importance of industry participation in conservation planning, strengthened by secure access to resources via statutory fishing rights, which provide critical incentives to invest in conservation. We therefore reflect on the potential application of this case to other remote large MPAs, highlighting potential directions for future research.